Pandemija covid-19 in uporabnost instituta spremenjenih okoliščin - Samec Berghaus, Nataša (Podjetje in delo, 2020)
In early 2020, the COVID-19 coronavirus pandemic caused drastic changes that raised a number of legal issues, including in contract law. Although countries have taken a number of partial measures to mitigate the effects of the pandemic, the rebus sic stantibus institution in particular will play a key role in the area of contract law. Therefore, in the case of measures to curb the COVID-19 epidemic, the article discusses the issue of the applicability and appropriateness of the regulation of the institute of changed circumstances in Slovenian legislation, especially from the point of view of whether the parties would like to maintain a contractual relationship. Therefore, the paper also analyses the comparative German regime. The Slovenian legal system - unlike the German regulation of business grounds (Geschäftsgrundlage) in paragraph 313 BGB - does not allow a request for modification of the contract due to changed circumstances to the affected party (it can only be offered by another party), which could benefit from it in the current situation (especially if permanent or partially fulfilled relationships are taken into account).
Keywords: business foundation; business grounds; changed circumstances; covid-19; epidemic; epidemije; lease; modification of the contract; najemne pogodbe; objection; poslovna podlaga; razveza pogodbe; rebus sic stantibus; sprememba pogodbe; spremenjene okoliščine; termination of the contract; the basis for the legal affair; ugovori